Development of models and algorithms for optimization of resource consumption in the data storage based on cloud platform - Мацуєва, Карина Андріївна (Technology audit and production reserves, 2015)
The use of cloud computing technology to build information systems of research organization is discussed in this paper. The main purpose is to determine the key parameters that affect how each resource involved in the construction of systems and optimization of resource consumption taking into account solvable problem. The research results are based on queuing theory, methods of optimization and simulation. Mathematical models of service requests users to store data on a cloud platform. Also the algorithm of load balancing algorithm and intellectual migration data in cloud storage data is developed. The algorithms allow scale information system without lowering the volume of resources involved in the work. Performance evaluation showed decrease query processing time by increasing system capacity by using developed technology. The research results can be used to improve the efficiency of software and hardware resources, quality of services in information systems to the cloud platform, as well as to avoid overloading services.